Face and content validity of a virtual-reality simulator for myringotomy with tube placement. Issue 1 (December 2015) - Huang, Caiwen; Cheng, Horace; Bureau, Yves; Agrawal, Sumit; Ladak, Hanif
Abstract Background Myringotomy with tube insertion can be challenging for junior Otolaryngology residents as it is one of the first microscopic procedures they encounter. The Western myringotomy simulator was developed to allow trainees to practice microscope positioning, myringotomy, and tube placement. This virtual-reality simulator is viewed in stereoscopic 3D, and a haptic device is used to manipulate the digital ear model and surgical tools. Objective To assess the face and content validity of the Western myringotomy simulator. Methods The myringotomy simulator was integrated with new modules to allow speculum placement, manipulation of an operative microscope, and insertion of the ventilation tube through a deformable tympanic membrane. A questionnaire was developed in consultation with instructing surgeons. Fourteen face validity questions focused on the anatomy of the ear, simulation of the operative microscope, appearance and movement of the surgical instruments, deformation and cutting of the eardrum, and myringotomy tube insertion. Six content validity questions focused on training potential on surgical tasks such as speculum placement, microscope positioning, tool navigation, ear anatomy, myringotomy creation and tube insertion. A total of 12 participants from the Department of Otolaryngology—Head and Neck Surgery were recruited for the study. Prior to completing the questionnaire, participants were oriented to the simulator and given unlimited time to practice until they were comfortable with all of its aspects. Results Responses to 12 of the 14 questions on face validity were predominantly positive. One issue of concern was with contact modeling related to tube insertion into the eardrum, and the second was with the movement of the blade and forceps. The former could be resolved by using a higher resolution digital model for the eardrum to improve contact localization. The latter could be resolved by using a higher fidelity haptic device. With regard to content validity, 64 % of the responses were positive, 21 % were neutral, and 15 % were negative. Conclusions The Western myringotomy simulator appears to have sufficient face and content validity. Further development with automated metrics and skills transference testing is planned.